2019
DOI: 10.18483/ijsci.2189
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Soil and Waterconservation Techniques to Soil Carbon Sequestration in a Forest Ecosystem in West Africa (Burkina Faso)

Abstract: Kuinima forest ecosystem, a classified forest, located in western Burkina Faso, is undergoing accelerated degradation due to climatic hazards and anthropogenic factors such as excessive cutting of trees, bush fires, etc. The main objective of this study is to assess the contribution of three water and soil conservation techniques (Zaï forest, stone rows, Zaï forest+ stone rows) to soil carbon sequestration and their impact on some soil physicochemical parameters. Thus, soil samples were taken, and the physicoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
0
0
3
Order By: Relevance
“…Bambara et al (2012) who investigated the effects of zaï, and stone bunds implemented for ten years, have concluded that duration alone does not permit to restore soil fertility. Besides, under a southsoudanian climate of western Burkina Faso, Zaï forest, Zaï forest + stone bunds and stone bunds treatments resulted in an increase of soil organic carbon stock by 166%, 77% and 21% in the 0-20 cm depth, respectively (Yameogo et al, 2019). It seems that the effect of the combination of FLR practices is not the same as the sum of the effects of each individual FLR practice.…”
Section: Introductionmentioning
confidence: 94%
“…Bambara et al (2012) who investigated the effects of zaï, and stone bunds implemented for ten years, have concluded that duration alone does not permit to restore soil fertility. Besides, under a southsoudanian climate of western Burkina Faso, Zaï forest, Zaï forest + stone bunds and stone bunds treatments resulted in an increase of soil organic carbon stock by 166%, 77% and 21% in the 0-20 cm depth, respectively (Yameogo et al, 2019). It seems that the effect of the combination of FLR practices is not the same as the sum of the effects of each individual FLR practice.…”
Section: Introductionmentioning
confidence: 94%
“…Toutefois, sa mise en oeuvre en Afrique subsaharienne rencontre d'énormes difficultés en raison de l'indisponibilité de données précises sur les émissions et les stocks de carbone des forêts (Dimobe et al, 2018). Les références traitant du stock de carbone le long de la rivière Kou sont quasiment inexistantes malgré de nombreuses études menées au Burkina Faso qui ont mis en exergue le potentiel de séquestration des plantations et peuplements agroforestiers et dans les sols (Coulibaly et al, 2018 ;Ouédraogo et al, 2019 ;Gomgnimbou et al, 2019 ;Yaméogo et al, 2019 ;Ganamé et al, 2021 ;Koala et al, 2021). Pourtant cet écosystème constituerait une importe source de séquestration de carbone.…”
Section: Introductionunclassified
“…De même, la matière organique est piégée au niveau des trous de zaï, réduisant ainsi les pertes par ruissellement. Plusieurs auteurs(8, 23 ; 24 ; 29) ont également montré que la technique du zaï avec apport de fumure organique et combinée ou pas à la réalisation des cordons pierreux amélioraient sensiblement les caractéristiques chimiques du sol.Les pratiques Zaï + FO et CP +Zaï+ FO ont permis d'augmenter la teneur en matière organique du sol respectivement de 23,19 % et 17,3 % par rapport au témoin absolu sur une période de trois ans(28). De même, la pratique du zaï sur une période de six ans a induit des augmentations de 38 % pour le carbone et de 31 % pour l'azote du sol(24).…”
unclassified
“…De même, la pratique du zaï sur une période de six ans a induit des augmentations de 38 % pour le carbone et de 31 % pour l'azote du sol(24). Yaméogo et al(28) ont montré que la combinaison des cordons pierreux au zaï et le zaï seul augmentaient la teneur en matière organique respectivement de 88,68 % et 113,21 % comparativement au témoin absolu après 10 ans sous forêt en zone sud-soudanienne du Burkina Faso. Ces auteurs précisent également que les teneurs d'azote ont quasiment doublé au cours de la même période pour les mêmes pratiques.…”
unclassified
See 1 more Smart Citation